Skin-impedance in Fabry disease: a prospective, controlled, non-randomized clinical study - Gupta, Surya N.; Ries, Markus (BMC neurology, 2008)
We previously demonstrated improved sweating after enzyme replacement therapy (ERT) in Fabry disease using the thermo-regularity sweat and quantitative sudomotor axon reflex tests. Skin-impedance, a measure skin-moisture (sweating), has been used in the clinical evaluation of burns and pressure ulcers using the portable dynamic dermal impedance monitor (DDIM) system.